Knut-Inge Klepp, Paul M. Biswalo & Aud Talle (red.): Young People at Risk. Fighting AIDS in Northern Tanzania. - Samuelsen, Helle (Tidsskriftet Antropologi, 1998)
Fighting AIDS in Northern Tanzania. Anmeldes af Helle Samuelsen.